2016
DOI: 10.1017/s0014479716000491
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF LIME AND PHOSPHORUS FERTILIZER ON ACID SOILS AND BARLEY (HORDEUM VULGARE L.) PERFORMANCE IN THE CENTRAL HIGHLANDS OF ETHIOPIA

Abstract: SUMMARYLow soil pH and associated soil infertility problems are considered to be amongst the major challenges to barley production in the highlands of Ethiopia. In response to this, an experiment was conducted at low soil pH (< 5 H2O) site on the effects of different levels of lime and phosphorus (P) fertilizer on soil pH, exchangeable aluminium (Al3+), grain yield and yield components of barley during 2010 and 2011 cropping seasons. The experiment comprised factorial combinations of five lime rates (0, 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 31 publications
2
44
3
Order By: Relevance
“…According to Agegnehu et al (2006) the application of lime at the rates of 1, 3 and 5 t ha -1 resulted significantly in linear response with mean faba bean seed yield advantages of 45, 77 and 81% over the control. Desalegn et al (2017) showed that application of 0.55, 1.1, 1.65 and 2.2 t lime ha -1 decreased Al 3+ by 0.88, 1.11, 1.20 and 1.19 mill equivalents per 100 g of soil, and increased soil pH by 0.48, 0.71, 0.85 and 1.1 units, respectively. Agegnehu et al (2006) also indicated that soil pH consistently increased from 4.37 to 5.91 as lime rate increased.…”
Section: A) Limingmentioning
confidence: 97%
“…According to Agegnehu et al (2006) the application of lime at the rates of 1, 3 and 5 t ha -1 resulted significantly in linear response with mean faba bean seed yield advantages of 45, 77 and 81% over the control. Desalegn et al (2017) showed that application of 0.55, 1.1, 1.65 and 2.2 t lime ha -1 decreased Al 3+ by 0.88, 1.11, 1.20 and 1.19 mill equivalents per 100 g of soil, and increased soil pH by 0.48, 0.71, 0.85 and 1.1 units, respectively. Agegnehu et al (2006) also indicated that soil pH consistently increased from 4.37 to 5.91 as lime rate increased.…”
Section: A) Limingmentioning
confidence: 97%
“…Horizonal lines show 90% (green) and 50% relative yield (red). The data used to construct these figures has been derived from (a) Bread Wheat (Adams, 1984a; Anderson & Bell, 2019; Brooke, Coventry, Reeves, & Jarvis, 1989; Caires, Correa, Churka, Barth, & Garbuio, 2006; Coventry, Slattery, Burnett, & Ganning, 1997; Doyle & Bradley, 1982; Farhoodi & Coventry, 2008; Fettell, Evans, Carpenter, & Brockwell, 2007; Johnson & Ohki, 1984; Kaitibie, Epplin, Krenzer, & Zhang, 2002; Kariuki et al, 2007; Li et al, 2001; Liu et al, 2004; Lollato, Edwards, & Zhang, 2013; Lollato, Ochsner, Arnall, Griffin, & Edwards, 2019; Mahler & McDole, 1987; Mead et al, 2003; Mullen, Scott, Evans, & Conyers, 2006; Rhoads & Manning, 1989; Scott, Conyers, Fisher, & Lill, 1992; Scott, Conyers, Poile, & Cullis, 1999; Slattery & Coventry, 1993; Slattery, Morrison, & Coventry, 1995; Tang, Nuruzzaman, et al, 2003; Tang, Rengel, Diatloff, & Gazey, 2003; Unruh, 1988); (b) Durum Wheat (Bona et al, 1995; Farhoodi & Coventry, 2008; Tang, Nuruzzaman, et al, 2003); (c) Barley (Brooke et al, 1989; Desalegn, Alemu, Adella, Debele, & Gonzalo, 2017; Dickson, Aitken, & Moody, 1995; Dolling, Porter, & Robson, 1991; Doyle & Bradley, 1982; Farhoodi & Coventry, 2008; Liu et al, 2004; Mahler & McDole, 1987; Mullen et al, 2006; Slattery et al, 1995; Slattery & Coventry, 1993; Tang, Rengel, Diatloff, & Gazey, 2003); (d) Triticale (Brooke et al, 1989; Doyle & Bradley, 1982; Li et al, 2001; Liu et al, 2004; Slattery et al, 1995; Slattery & Coventry, 1993); (e) Sorghum (Adams, 1984a; Baligar et al, 1989; Butchee et al, 2012; Duncan, Dobson, & Fishe...…”
Section: Resultsmentioning
confidence: 99%
“…While millet is often considered to be one of the most salt tolerant species, there is wide variation reported in the tolerance of different millet species and cultivars (Dua, 1989;Kafi et al, 2009;Kumar et al, 2018), and few studies compared the performance of millet with other crops. Maize has been observed to be less The data used to construct these figures has been derived from (a) Bread Wheat (Adams, 1984a;Anderson & Bell, 2019;Brooke, Coventry, Reeves, & Jarvis, 1989;Caires, Correa, Churka, Barth, & Garbuio, 2006;Coventry, Slattery, Burnett, & Ganning, 1997;Doyle & Bradley, 1982;Farhoodi & Coventry, 2008;Fettell, Evans, Carpenter, & Brockwell, 2007;Johnson & Ohki, 1984;Kaitibie, Epplin, Krenzer, & Zhang, 2002;Kariuki et al, 2007;Li et al, 2001;Liu et al, 2004;Lollato, Edwards, & Zhang, 2013;Lollato, Ochsner, Arnall, Griffin, & Edwards, 2019;Mahler & McDole, 1987;Mead et al, 2003;Mullen, Scott, Evans, & Conyers, 2006;Rhoads & Manning, 1989;Scott, Conyers, Fisher, & Lill, 1992;Scott, Conyers, Poile, & Cullis, 1999;Slattery & Coventry, 1993;Slattery, Morrison, & Coventry, 1995;Tang, Nuruzzaman, et al, 2003;Tang, Rengel, Diatloff, & Gazey, 2003;Unruh, 1988); (b) Durum Wheat (Bona et al, 1995;Farhoodi & Coventry, 2008;Tang, Nuruzzaman, et al, 2003); (c) Barley (Brooke et al, 1989;Desalegn, Alemu, Adella, Debele, & Gonzalo, 2017;…”
Section: Cerealsmentioning
confidence: 99%
“…Previous studies (Table 4) indicated that application of different rates of lime and P fertilizer significantly increased barley grain yield in the central highlands of Ethiopia (Beyene, 1987;Desalegn et al, 2017). According to Desalegn et al (2017), the combined application of 1.65 t lime ha -1 and 30 kg P ha -1 resulted in 133% more grain yields of barley than the control (without P and lime).…”
Section: Management Of Soil Aciditymentioning
confidence: 92%